2012
DOI: 10.1038/npp.2012.11
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Corticosterone Exposure during Adolescence Reduces Impulsive Action but Increases Impulsive Choice and Sensitivity to Yohimbine in Male Sprague-Dawley Rats

Abstract: Chronic stress during adolescence is associated with an increased risk for alcoholism and addictive disorders. Addiction is also associated with increased impulsivity, and stress during adolescence could alter cortical circuits responsible for response inhibition. Therefore, the present study determined the effect of chronic exposure to the stress hormone corticosterone (CORT) during adolescence on tests of impulsivity in adulthood and examined possible biochemical mechanisms. Male Sprague-Dawley rats were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 61 publications
8
45
1
Order By: Relevance
“…Corticosterone levels were increased in control lactating rats twenty days after delivery, while AVP deficiency dampened this increase, a finding that is consistent with earlier reports (Fodor et al, 2013).These data might suggest that AVP contributes, in part, to maternal increases in impulsivity via the enhancement of HPA axis activity, as earlier reports showed that chronic corticosterone treatment leads to increased impulsivity (Torregrossa et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Corticosterone levels were increased in control lactating rats twenty days after delivery, while AVP deficiency dampened this increase, a finding that is consistent with earlier reports (Fodor et al, 2013).These data might suggest that AVP contributes, in part, to maternal increases in impulsivity via the enhancement of HPA axis activity, as earlier reports showed that chronic corticosterone treatment leads to increased impulsivity (Torregrossa et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…In addition to measurements of impulsive behavior, HPA axis activity (i.e. corticosterone levels) was also assessed, as the HPA axis has been reported to be altered by AVP deficiency (Fodor et al, 2013;Makara et al, 2012) and to play a role in impulsivity (Torregrossa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to impulsive discounting, the prefrontal and subcortical circuits are largely those that have been implicated with discounting decision making in fMRI research (Bickel et al 2009, McClure et al 2004), suggesting that commensurate impairment in discounting may be a behavioral manifestation of these neuroadaptive changes. With regard to the antireward system, the role of stress in discounting has been only modestly studied, and results are mixed (Diller et al 2011, Fields et al 2009, Torregrossa et al 2012, White et al 2008). However, purely from conjecture, given the laboratory evidence on withdrawal effects discussed above, the chronic augmentation of the antireward system may be a further plausible mechanism for increasing discounting.…”
Section: Processes Engendering Reinforcer Pathologymentioning
confidence: 99%
“…Stress across the lifespan has been shown to increase the likelihood of alcohol use disorders (Enoch, 2011). In animal models, chronic activation of stress circuitry can promote the development of behaviors that are thought to phenotypes that are associated with early onset of drinking in humans (Hamilton, Ansell, Reynolds, Potenza, & Sinha, 2013; Torregrossa, Xie, & Taylor, 2012). In addition to driving behavioral inflexibility, prevailing theories suggest that alcohol use disorders represent reward surfeit disorders (Comings & Blum, 2000; Koob, 2013) in which an impaired ‘reward system’ promotes the development of addiction.…”
Section: Stress Effects On Habitmentioning
confidence: 99%